Bridging the gap: safety and outcomes of intensivist-led ECMO retrievals - Mihu, Mircea R.; Maybauer, Marc O.; Cain, Kaitlyn; Swant, Laura V.; Harper, Michael D.; Schoaps, Robert S.; Brewer, Joseph M.; Sharif, Ammar; Benson, Clayne; El Banayosy, Ahmed M.; El Banayosy, Aly (Frontiers in Medicine, 2023)
Purpose Most extracorporeal membrane oxygenation (ECMO) cannulations are performed by cardiothoracic surgeons (CTS). Due to an increase in utilization of ECMO and limited availability of CTS, there is a mismatch between ECMO demand and CTS accessibility for remote cannulations. We report our intensivist-led program’s experience in remote ECMO cannulations, retrievals, complications, and outcomes. Materials and methods A prospective, single-center, observational study was performed on patients that required ECMO cannulation at the referring facilities and were transported to our institution between program initiation, on October 1, 2014 to September 30, 2022. Results were presented as mean ± SD, median (min – max) or number (%). Results Since program commencement, 305 patients were accepted for ECMO retrieval. Three hundred and three patients were placed on ECMO at the 47 referring hospitals among 5 states. In our study, 185 (61%) patients required veno-arterial ECMO and 115 (38%) were placed on veno-venous ECMO. Three patients (1%) were cannulated for veno-arteriovenous ECMO. Twenty patients were cannulated under cardio-pulmonary resuscitation. Most of the patients were transported by ambulance (79%), 14% by helicopter, and 7% by airplane. Six out of the 303 patients did not leave the referring facility. All patients that left the referring hospitals arrived safely to our institution. No major complications occurred in route. Conclusion Our study’s findings indicate that non-CTS physicians can successfully cannulate and retrieve patients with a low complication profile.